Analysis of Coworkers, Awards, and Work Environment on Job Satisfaction of ASN Employees at the Regional Office of the Ministryof Religion of North Sumatra Province - Rafika Anggraini; Desi Astuti; Muhammad Toyib Daulay (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study was conducted to examine the effects of coworkers, rewards, and the work environment on the level of job satisfaction among Civil Servants (ASN) at the Regional Office of the Ministry of Religious Affairs of North Sumatra Province. The research employed a quantitative associative approach using multiple linear regression analysis. The research population consisted of all civil servants totaling 173 employees, while the sample comprised 64 employees selected using the Slovin formula and determined through purposive sampling techniques. Research data were collected through questionnaire distribution in 2025 and were subsequently analyzed using SPSS version 24.0. The results indicated that coworkers, rewards, and the work environment had positive and significant effects on employee job satisfaction, both partially and simultaneously. The regression analysis produced the equation Y = 2.856 + 0.300X₁ + 0.307X₂ + 0.296X₃ + e. Partial testing showed that the coworker variable obtained a t-value of 2.659 with a significance level of 0.010, the reward variable achieved a t-value of 2.813 with a significance level of 0.007, and the work environment variable recorded a t-value of 2.757 with a significance level of 0.008. Furthermore, the simultaneous test resulted in an F-value of 93.218 with a significance level of 0.000. All hypotheses proposed in this study were proven and accepted, as the testing results were consistent with the initial research assumptions. The findings also revealed that the reward variable was the most dominant factor influencing employee job satisfaction compared to the other variables. Approximately 81.5% of the variation in job satisfaction could be explained by the combined influence of coworkers, rewards, and the work environment, indicating a very strong relationship. These results suggested that fairness in compensation, clarity of reward mechanisms, and recognition of individual contributions played a crucial role in shaping employees’ evaluations of their work.